Iatrogenic fractures of teeth (LLC "Endo Press", 2020)
The results of medical practice dentists associated with the peculiarities of restoration and prosthetics, can create conditions for «iatrogenic fracture of teeth». The aim of this study was to analyze the causes and make recommendations for the prevention and treatment of iatrogenic fractures optimal teeth. The study included 15 patients with fractures of the teeth after the conducted early therapeutic and orthopedic treatment. Tooth extraction and implantation carried out under local anesthesia with the use of implants ITI Standard Plus SLA and SLActive (Straumann, Switzerland). Osteoplasty held collagen material without the use of barrier membranes. Prosthetics have implemented fixed prosthetic ceramic designs. Analysis of the clinical, radiological, statistical and empirical. All fractures of the teeth (incisors, 33%; premolars, 20%; molars, 40%; Fang, n = 1), iatrogenic origin is longitudinal. The cause of the fracture molars had an extensive restoration without artificial crowns and superkontakt antagonist. The premolars were damaged due to the actions Expander wedge copings, canine and incisors - due to occlusal overload. Obvious signs of fracture on radiographs were: a gap (n = 7; 47%), the difference fragments (n = 4, 27%) and bone loss on the perimeter of the root (n = 4, 27%). Ability to save teeth with longitudinal fracture was not seen. Orthopedic rehabilitation in 8 cases (54%) held by means of implantation. Iatrogenic fractures of the teeth can be considered a conditional term, recalls the need to comply with standards preparation, restoration and prosthetics. Rational method of rehabilitation of patients with fractures of the tooth implant prosthetics is that it is not always possible for subjective reasons.